2019
DOI: 10.4103/ojo.ojo_200_2017
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for endothelial cell damage in diabetics after phacoemulsification

Abstract: BACKGROUND: To assess the corneal endothelium, central corneal thickness and the factors associated with endothelial cell damage after phacoemulsification in diabetics in comparison with non-diabetics METHODS: It was a case control study with 80 eyes each in the diabetic group and the control group. Intraoperative mydriasis, effective phaco time (EPT) and postoperative inflammation were measured. Preoperative, 1 st week, 6 th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
0
17
1
Order By: Relevance
“…The reason for this is that, unlike previous studies, this study observed a relatively extended period of 1 year after surgery, and as a result, it is assumed that the central ECD recovered due to stabilization of the endothelium following a period of rearrangement. [ 31 , 32 ] According to the recently reported studies of Ganesan et al [ 13 ] and Fernández-Muñoz et al, [ 14 ] ECD loss at 3 months after cataract surgery did not differ between diabetes and control groups. Further studies with large sample sizes are required.…”
Section: Discussionmentioning
confidence: 94%
“…The reason for this is that, unlike previous studies, this study observed a relatively extended period of 1 year after surgery, and as a result, it is assumed that the central ECD recovered due to stabilization of the endothelium following a period of rearrangement. [ 31 , 32 ] According to the recently reported studies of Ganesan et al [ 13 ] and Fernández-Muñoz et al, [ 14 ] ECD loss at 3 months after cataract surgery did not differ between diabetes and control groups. Further studies with large sample sizes are required.…”
Section: Discussionmentioning
confidence: 94%
“…The cornea has been reported to be thicker in eyes of diabetic patients than in eyes of non-diabetic subjects. 8 Cataract extraction and IOL implantation causes trauma to the already compromised corneal endothelium and causes corneal edema. Hence compared with non-diabetic patients, eyes of diabetic patients showed more damage in corneal endothelial cells after cataract surgery and a delay in the post-operative recovery of corneal edema.…”
Section: Resultsmentioning
confidence: 99%
“…Decreased innervation, exposure to vitreous humor [ 32 ], increased hardness of lens nucleus [ 14 ], surgical trauma [ 33 ], intraoperative inflammatory response [ 15 ], and postoperative corneal edema [ 34 ] are important risk factors for CECs damage after phacoemulsification. However, the risk of CECs injury caused by the above factors increases in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress not only directly damages CECs [ 29 ] but also induces inflammation through multiple activation pathways [ 40 ]. Corneal edema alleviates with a decrease in inflammation, resulting in a lower CCT during the recovery process after phacoemulsification [ 15 ].…”
Section: Discussionmentioning
confidence: 99%